SAYURAN ORGANIK LAHAN KERING UNTUK PARIWISATA DI DOMPU - A. Farid Hemon (Jurnal SIAR ILMUWAN TANI, 2021)
This science and technology application was carried out to educate partner farmers (1) “Mada Kabuntu Farmer Group" and (2) "Sinar Rinjani Farmer Group" to increase the production of organic vegetables in dry land. To achieved this goal, training activities and plot demonstration have been carried out. The training method used was the adult education method with participatory techniques. The training participants were members of the farmers group "Mada Kabuntu" and "Sinar Rinjani". Training activities include pre-test, delivery and explanation of modules (with LCD and props), discussion and question and answer. Plot demonstrations and organic vegetable cultivation practices were carried out on farmers' land. Farmers were participatively involved jointly from planning, implementing and evaluating of harvest yield. The activity results showed that the farmers participating in this program were very responsive to the development of organic vegetables on dry land. The participating farmers were actively working together to carried out all phases of activities from training, demonstration plots from planting, plant maintenance and harvesting. The results of these activities indicated that there has been a technology transfer process for developing organic vegetables in the dry land Dompu district.